2005
DOI: 10.1021/nl051899r
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Mediated Formation of Single-Wall Carbon Nanotube Composites

Abstract: The formation of silica- and titania-coated single-wall carbon nanotubes (SWNTs) using a mutlifunctional peptide to both suspend SWNTs and direct the precipitation of silica and titania at room temperature is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
171
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(177 citation statements)
references
References 34 publications
6
171
0
Order By: Relevance
“…Aptamer-functionalized nanotube electrodes have been shown to detect single bacterial cells in real time 26 . Further, we have recently shown that phage display can be utilized to determine peptide sequences that selectively bind to CNTs and graphene 8,[27][28][29] . This has enabled the generation of bifunctional peptides containing a carbon nanomaterial recognition moiety combined with an analyte binder to non-covalently selfassemble and impart selectivity on graphene sensor arrays.…”
mentioning
confidence: 99%
“…Aptamer-functionalized nanotube electrodes have been shown to detect single bacterial cells in real time 26 . Further, we have recently shown that phage display can be utilized to determine peptide sequences that selectively bind to CNTs and graphene 8,[27][28][29] . This has enabled the generation of bifunctional peptides containing a carbon nanomaterial recognition moiety combined with an analyte binder to non-covalently selfassemble and impart selectivity on graphene sensor arrays.…”
mentioning
confidence: 99%
“…These data presented herein will then be used to help interpret the adsorption behaviour of a known graphene-binding peptide, P1, and its mutant analogue, P1A3. 10,37,68 Simulations of P1 and P1A3 adsorbed at a graphene interface, have been reported previously. 10,37,39,69 However, none of these previous studies used a polarisable FF, or made use of any advanced conformational sampling approaches.…”
Section: Introductionmentioning
confidence: 76%
“…The library members, detailed in Table 1, range in length from 7-59 amino acids and encode a wide variety of functions such as binding to various inorganic substrates (GBP, CNBP, QBP, MBD and AFP8), nucleation of mineral and metallic nanostructures (A3, CLP12, CT43 and Mms6), and a highly specific catalytic interaction with a protein (SpyTag) 15,[21][22][23][24][25][26][27][28][29][30][31] . Each peptide domain was cloned as C-terminal fusions to CsgA with an intervening six-amino-acid flexible linker (Table 1) and these plasmids were expressed in LSR10 cells to produce 12 different BIND biofilms.…”
Section: Csga Peptide Fusions Retain Amyloid Self-assembly Functionmentioning
confidence: 99%